Nilai-nilai Pendidikan Akhlak bagi Anak dalam “Serial Animasi Nussa dan Rara” pada Episode “Kamu… Antta” - Gustami, Harmita; Saputra, Edi (YASIN, 2025)
Moral education plays an important role in life to realize the personality and noble character of each individual. Without good morals, a person can harm themselves and others. The emergence of the animation Nussa and Rara is regarded as providing good education for children. This study used content analysis methods to obtain data regarding the values of moral education for children, specifically morals towards Allah Swt. and morals towards oneself, using the episode “Kamu… Antta” as a sample. The instrument in this study is the human instrument, and data collection techniques were carried out through coding sheets and literature studies. The data analysis techniques used include filling in the coding sheets according to the established measuring tools, validity testing, and organizing data into units of analysis so that it can be categorized and interpreted to draw conclusions from the research. The results of the study indicate that in the animation Nussa and Rara, there are values of moral education towards Allah Swt. and morals towards oneself.